Genotoxic and Cytotoxic Effects of Testosterone Undecanoate on Bone Marrow and Germ Cells in Mice - Shafi, Farha (Jordan Journal of Pharmaceutical Sciences, 2016)
Anabolic androgenic steroids are synthetic compounds used for treatment of numerous medical condition as well as being used widely by athletes performance enhancers and bodybuilding. The aim of the present study was evaluate the genotoxic and cytotoxic effects of testosterone undecanoate in a mouse model, chromosomal aberrations, mitotic index of bone marrow cells, mitotic index of spermatocytes sperm head abnormality. This effect were determined after the administration of a 0.01mg of testosterone undecanoate via oral gavage for 30 days. Result revealed that testosterone undecanoate caused a slight increase in the frequency of chromosomal aberrations and a significant reduction of mitotic index of bone marrow cells. Despite that, there was no significant increase in percentage of sperm head abnormality in male mice. Those findings were parallel to a significant reduction in mitotic index of spermatocytes when compared to negative control group and positive control group. This study documents that testosterone undecanoate has cytotoxic effects on bone marrow and germ cells of male mice.